POLA PENDIDIKAN AKHLAK PADA ANAK PRAREMAJA DI LINGKUNGAN KELUARGA (STUDI KASUS DI KEL. TALANG SALING KEC. SELUMA KAB. SELUMA PROPINSI BENGKULU) - Budi Erliyanto (IAIN Bengkulu, 2017)
Gutter Saling is a village located in Seluma is located in the District Seluma District, which has made the expansion in2003, which split from South Bengkulu, the result of the division, is certainly going to change the order of life, whether from the government, in terms of revenue, culture, infrastructure, people’s behavior, both in terms of children ages pre-teens, teens, adults, or even parents themselves, so that with the changes become Seluma, people in the Village of Salado Saling into society began gradually leave traditional traditions that have been there, so do not have a traditional or a new life style, resulting in behavior or morals are not good in everyday life, which ultimately lead to non selarasan in behavior. This study used a qualitative descriptive approach. In obtaining the data, the authors using observation, interviews, and documentation of previous research. From the research inidi get the result that moral education is adopted by parents in the family in child preteen in the Village of Talang Saling District of Seluma not been implemented properly by parents who have children with pre-teens, because there are many parents who do not implement it, most parents just rebuked him away without giving punishment to his son. As well as the pattern of moral education of children of pre teen in the family environment Village of Talang Saling District of Seluma applied by parents is lacking once adopted by parents in the family environment, these are all visible from the percentage of parents just give the pattern direction, that each what we do have consequences, should the parents were able to give firmness to provide education to their children so that the pattern can be complied with and implemented in everyday life